Pembuatan Mesin Penyegel Gelas Plastik (Cup Sealer) Semi Otomatis - Fuad Hamzah; Prantasi Harmi Tjahjanti; Wiwik Sumarmi; Henry Vian Ivanda (Institute for Research and Community Services, 2023)
Clear water that has been processed into ready to drink in Sumbegedang Pasuruan village cannot yet be distributed to the local village community or other villages, because there is still no equipment for the process of packaging clean ready-to-drink water. Therefore, in this Community Service Activity, a semi-automatic plastic cup sealing machine was made with the sealing mechanism run by a driving dynamo (AC motor) with a push button connected to a microcontroller as the trigger. This Community Service activity is a continuation of Community Service activities in the village of Sumbergedang, Pasuruan which has abundant clear water originating from Mount Penanggungan and has been processed into clean water ready to drink. Clean water that has been placed in a plastic glass container, then for the future can be produced or distributed to the local village community or other villages. Automatic components used for the manufacture of semi-automatic cup sealer machines are PCB, ATMEGA48V-10PU IC, step down transformer, thermostat, heater, digital counter, push button, timer potentiometer, limit switch, relay, PCB cable, motor AC. The machine is only used for one size of 7 oz glass. A machine operation test was carried out to find out if this semi-automatic cup sealer machine met the machine's standard results. Furthermore, an introduction was made along with the process of operating this semi-automatic plastic cup sealing machine to the people of Sumbergedang Pasuruan village. The results show that this semi-automatic cup sealer can be used in the field and for the process of packing clean, ready to drink water in Sumbergedang Village, Pasuruan.